Structural Variations in the Central Heterocyclic Scaffold of Tripartite 2,6-Difluorobenzamides: Influence on Their Antibacterial Activity against MDR Staphylococcus aureus - Thibaut Barbier; Cédric Badiou; Floriane Davy; Yves Queneau; Oana Dumitrescu; Gérard Lina; Laurent Soulère (Molecules, 2022)
Five series of heterocyclic tripartite 2,6-difluorobenzamides, namely 1,2,3-triazoles, 1,2,4- and 1,3,4-oxadiazoles, analogs of reported model anti-staphylococcal compounds, were prepared. The purpose was to investigate the influence of the nature of the heterocyclic central scaffold on the biological activity against three strains of S. aureus, including two drug-resistant ones. Among the 15 compounds of the new collection, a 3-(4-tert-butylphenyl)-1,2,4-oxadiazole linked via a methylene group with a 2,6-difluorobenzamide moiety (II.c) exhibited a minimal inhibitory concentration between 0.5 and 1 µg/mL according to the strain. Subsequent studies on II.c demonstrated no human cytotoxicity, while targeting the bacterial divisome.